Experimental peripheral arterial disease: new insights into muscle glucose uptake, macrophage, and T‐cell polarization during early and late stages - Pellegrin, Maxime (Wiley Periodicals, Inc., 2014)
Peripheral arterial disease (PAD) is a common disease with increasing prevalence, presenting with impaired walking ability affecting patient's quality of life. PAD epidemiology is known, however, mechanisms underlying functional muscle impairment remain unclear. Using a mouse PAD model, aim of this study was to assess muscle adaptive responses during early (1 week) and late (5 weeks) disease stages. Unilateral hindlimb ischemia was induced in ApoE(−/−) mice by iliac artery ligation. Ischemic limb perfusion and oxygenation (Laser Doppler imaging, transcutaneous oxygen pressure assessments) significantly decreased during early and late stage compared to pre‐ischemia, however, values were significantly higher during late versus early phase. Number of arterioles and arteriogenesis‐linked gene expression increased at later stage. Walking ability, evaluated by forced and voluntary walking tests, remained significantly decreased both at early and late phase without any significant improvement. Muscle glucose uptake ([18F]fluorodeoxyglucose positron emission tomography) significantly increased during early ischemia decreasing at later stage. Gene expression analysis showed significant shift in muscle M1/M2 macrophages and Th1/Th2 T cells balance toward pro‐inflammatory phenotype during early ischemia; later, inflammatory state returned to neutrality. Muscular M1/M2 shift inhibition by a statin prevented impaired walking ability in early ischemia. High‐energy phosphate metabolism remained unchanged (31‐Phosphorus magnetic resonance spectroscopy). Results show that rapid transient muscular inflammation contributes to impaired walking capacity while increased glucose uptake may be a compensatory mechanisms preserving immediate limb viability during early ischemia in a mouse PAD model. With time, increased ischemic limb perfusion and oxygenation assure muscle viability although not sufficiently to improve walking impairment. Subsequent decreased muscle glucose uptake may partly contribute to chronic walking impairment. Early inflammation inhibition and/or late muscle glucose impairment prevention are promising strategies for PAD management.